Waterborne epoxy high build coating and preparation method thereof

Through the synergy between specific components and cashew shell oil-modified phenoamine curing agent, the solid content and construction performance of water-based epoxy thick slurry coatings are improved, and the problems of low solid content and carcinogens in traditional water-based coatings are solved, achieving efficient construction and Excellent salt spray resistance.

CN116376400BActive Publication Date: 2025-01-14ZHEJIANG TRANSFER PAINT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310387507.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-01-14
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

Traditional water-based coatings have low solid content, poor construction performance, and contain carcinogen epoxypropane, which leads to environmental pollution and health risks, has a long construction cycle, and insufficient salt spray resistance.

Method used

Using water-based epoxy thick slurry coating, the solid content and construction performance are improved through the synergy between component A of specific components and proportions and cashew shell oil-modified phenoamine curing agent, avoiding epoxypropane, and using nanocomposite dispersion Body and optimize emulsifiers to reduce viscosity and increase solids content.

Benefits of technology

It has achieved water-based epoxy thick slurry coatings with solid content up to 70%, fast drying speed, no easy cracks, shortened construction cycle, low VOC content, green and environmentally friendly, excellent salt spray resistance, and good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004179923250000131
    Figure BDA0004179923250000131
Patent Text Reader

Abstract

The present invention relates to a water-based epoxy thick paste coating and a preparation method thereof. The water-based epoxy thick paste coating comprises component A and component B; wherein component A comprises 30%-40% of water-based epoxy emulsion, 3%-10% of water-based nanocomposite dispersion slurry, 20%-50% of filler, 4%-15% of auxiliary agent and 5%-25% of water, the water-based epoxy emulsion comprises 2%-8% of water-based epoxy emulsifier, 60%-70% of first epoxy resin, 5%-18% of organic solvent and 20%-30% of water, the water-based epoxy emulsifier is an adduct of a second epoxy resin and an emulsifier, and the emulsifier is selected from a polyetheramine emulsifier or a nonionic emulsifier; component B is a cashew shell oil-modified phenolic amine curing agent. The water-based epoxy thick paste coating has a solid content of more than 70%, low VOC content, green environmental protection, excellent salt spray resistance, and has unique construction advantages such as high film thickness in one application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a waterborne epoxy thick paste coating and a preparation method thereof. Background Art

[0002] Traditional industrial coatings contain a large amount of organic solvents at the construction viscosity. During the coating construction and drying process, the volatilization of organic solvents not only causes a large amount of resource waste and environmental pollution, but also poses a fire hazard and endangers the health of construction workers. For this reason, it is advocated to develop environmentally friendly coatings such as solvent-based high-solid coatings, solvent-free coatings, water-based coatings and powder coatings.

[0003] Among them, although solvent-based high-solid coatings or solvent-free coatings reduce the volatilization of solvents, they generally have high viscosity and poor construction performance. At the same time, due to the small molecular weight and high cross-linking density of the film-forming resin, the coating is brittle; while the production process of powder coatings is relatively complicated, the manufacturing cost is high, and professional equipment is required for coating. The baking temperature is high, which will cause a lot of energy loss. Water-based coatings use water as a solvent and have good fluidity. They can not only save a lot of organic solvents, are green and pollution-free, but also have low selectivity for the construction environment and can be constructed on wet surfaces and humid environments. However, in order to ensure the dispersion effect of the resin in the water solvent, a large amount of water solvent is required, resulting in a low solid content of the water-based coating. Thick coating will cause the coating to not dry completely and cracks to form, and multiple recoatings are required in actual applications, resulting in a long construction cycle. In addition, the water-based epoxy resin used in traditional water-based coatings needs to be used in conjunction with epichlorohydrin, which is a Class 2A carcinogen and has high restrictions in production, storage and use. Summary of the invention

[0004] Based on this, it is necessary to provide a water-based epoxy thick paste coating and a preparation method thereof to address the above problems; the water-based epoxy thick paste coating has a solid content of more than 70%, a low VOC content, is green and environmentally friendly, has excellent salt spray resistance, and has unique construction advantages such as high film thickness in one application.

[0005] A water-based epoxy high build paint comprises a component A and a component B;

[0006] Wherein, the component A comprises 30%-40% of aqueous epoxy emulsion, 3%-10% of aqueous nanocomposite dispersion slurry, 20%-50% of filler, 4%-15% of auxiliary agent and 5%-25% of water, the aqueous epoxy emulsion comprises 2%-8% of aqueous epoxy emulsifier, 60%-70% of first epoxy resin, 5%-18% of organic solvent and 20%-30% of water, the aqueous epoxy emulsifier is an adduct of second epoxy resin and emulsifier, and the emulsifier is selected from polyetheramine emulsifier or nonionic emulsifier;

[0007] The B component is a cashew nut shell oil modified phenolic amine curing agent.

[0008] In one embodiment, when the waterborne epoxy mastic coating is used, the mass ratio of component A to component B is 5:1-8:1.

[0009] In one embodiment, the water-based epoxy emulsifier is an adduct of a second epoxy resin and an emulsifier in a mass ratio of 3:1-5:1.

[0010] In one embodiment, the D of the waterborne epoxy emulsion is 50 62.5nm-75.5nm;

[0011] And / or, the epoxy equivalent of the aqueous epoxy emulsion is 650-1200;

[0012] And / or, the viscosity of the aqueous epoxy emulsion is 500cps-2000cps.

[0013] In one embodiment, the first epoxy resin is selected from at least one of solid E20 epoxy resin, E44 epoxy resin, and E51 epoxy resin;

[0014] And / or, the second epoxy resin is selected from at least one of solid E20 epoxy resin, E44 epoxy resin, and E51 epoxy resin.

[0015] In one embodiment, the polyetheramine emulsifier is selected from M3085 polyetheramine emulsifier, and the nonionic emulsifier is selected from PLR1801C nonionic emulsifier or NP8836 polyether nonionic emulsifier.

[0016] In one embodiment, the aqueous nanocomposite dispersion slurry includes nanopowder, aqueous wetting dispersant and water, and the solid content of the aqueous nanocomposite dispersion slurry is 20%-40%.

[0017] In one embodiment, the particle size of the nanopowder is 50nm-100nm.

[0018] In one embodiment, the filler includes a physical filler and an anti-rust filler, and the mass ratio of the physical filler to the anti-rust filler is 5:4-15:4.

[0019] In one embodiment, the A component includes 30%-40% aqueous epoxy emulsion, 3%-10% aqueous nanocomposite dispersion slurry, 12%-30% physical filler, 8%-20% anti-rust filler, 0.5%-1% cosolvent, 0.2%-1% defoamer, 1%-2% dispersant, 0.2%-1% wetting agent, 0.2%-1% toughening agent, 0.2%-1% mildewproofing agent, 0.2%-1% neutralizing agent, 0.5%-2% film former, 0.5%-2% anti-flash rust agent, 0.5%-2% rheological additive and 5%-25% water.

[0020] The waterborne epoxy thick paste coating of the present invention, through the synergistic effect of component A having specific composition and ratio and cashew nut shell oil modified phenolic amine curing agent, on the one hand, not only makes the solid content of the waterborne epoxy thick paste coating as high as 70% or more, but also dries quickly and is not prone to cracking during the thick coating process, and has unique construction advantages such as high film thickness in one application, so that it can be used as a good thick paste primer, mid-coat or base-top all-in-one paint, and can greatly shorten the construction period and reduce the labor construction cost while ensuring the construction thickness; on the other hand, the waterborne epoxy thick paste coating has a low VOC content and is green and environmentally friendly, and does not contain carcinogens such as epichlorohydrin, is non-toxic and harmless, and the cured paint film has excellent performance and has long-lasting salt spray resistance and mechanical properties. DETAILED DESCRIPTION

[0021] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0023] The present invention provides a waterborne epoxy thick paste coating, comprising component A and component B;

[0024] Wherein, the component A comprises 30%-40% of aqueous epoxy emulsion, 3%-10% of aqueous nanocomposite dispersion slurry, 20%-50% of filler, 4%-15% of auxiliary agent and 5%-25% of water, the aqueous epoxy emulsion comprises 2%-8% of aqueous epoxy emulsifier, 60%-70% of first epoxy resin, 5%-18% of organic solvent and 20%-30% of water, the aqueous epoxy emulsifier is an adduct of second epoxy resin and emulsifier, and the emulsifier is selected from polyetheramine emulsifier or nonionic emulsifier;

[0025] The B component is a cashew nut shell oil modified phenolic amine curing agent.

[0026] Specifically, the water-based epoxy emulsifier is an adduct of the second epoxy resin and the emulsifier, which means that the water-based epoxy emulsifier is the reaction product of the second epoxy resin and the emulsifier. When the emulsifier is selected from the polyetheramine emulsifier, the polyetheramine with a monofunctional primary amine as the terminal group is reacted with the epoxy group to form an epoxy-polyether monoamine compound. In the chemical structure of the epoxy-polyether monoamine compound, the epoxy segment is used as the hydrophobic end and the polyether segment is used as the hydrophilic end. As a water-based epoxy emulsifier, it is beneficial to reduce the viscosity of the water-based epoxy emulsion and increase the solid content of the water-based epoxy emulsion. When the emulsifier is selected from the non-ionic emulsifier, it can react and crosslink with the epoxy resin to a certain extent, so that the density of the cured crosslinking is higher, thereby providing good paint film performance.

[0027] Thus, the reaction product of the second epoxy resin and the emulsifier is used as the water-based epoxy emulsifier, and the ratio of the water-based epoxy emulsifier, the first epoxy resin, the organic solvent and water is coordinated to form a water-based epoxy emulsion with a high solid content of 66%-72% and a low emulsion viscosity. At the same time, the cashew nut shell oil-modified phenolic amine curing agent with a solid content greater than or equal to 97% and a viscosity of 500cps-800cps is coordinated to significantly increase the overall volume solid content of component A and component B after mixing.

[0028] Furthermore, through the synergistic effect of component A with specific composition and ratio and component B of cashew nut shell oil modified phenolic amine curing agent, on the one hand, not only the solid content of waterborne epoxy thick paste coating is as high as more than 70%, but also the coating process is fast drying and not prone to cracking, with unique construction advantages such as high film thickness in one application, so it can be used as a good thick paste primer, mid-coat or base-top paint. On the premise of ensuring the construction thickness, it can greatly shorten the construction period and reduce the labor construction cost; on the other hand, waterborne epoxy thick paste coating has low VOC content and is green and environmentally friendly. It does not contain carcinogens such as epichlorohydrin, is non-toxic and harmless, and the cured paint film has excellent performance and has long-lasting salt spray resistance and mechanical properties.

[0029] Furthermore, the cashew nut shell oil-modified phenolic amine curing agent is preferably cashew nut shell oil-modified phenolic amine curing agent HD-5003.

[0030] In order to obtain a waterborne epoxy emulsifier with better emulsification performance, thereby further increasing the solid content of the waterborne epoxy emulsion, the waterborne epoxy emulsifier is preferably an adduct of a second epoxy resin and an emulsifier in a mass ratio of 3:1-5:1.

[0031] Specifically, the second epoxy resin is selected from at least one of solid E20 epoxy resin, E44 epoxy resin, and E51 epoxy resin, preferably solid E20 epoxy resin, the polyetheramine emulsifier is selected from M3085 polyetheramine emulsifier, and the nonionic emulsifier is selected from PLR1801C nonionic emulsifier or NP8836 polyether nonionic emulsifier.

[0032] It should be noted that, in the actual preparation process, the emulsifier can be modified according to other performance requirements of the coating product, such as hydrophobic modification of the M3085 polyetheramine emulsifier, which is more conducive to improving the water resistance of the coating, etc. The present invention is not limited to this.

[0033] Considering the influence of the physical and chemical indexes of waterborne epoxy emulsion on the performance of waterborne epoxy thick paste coating, in order to further improve the film-forming property, permeability and stability of waterborne epoxy thick paste coating, it is preferred that the D 50 is 62.5nm-75.5nm; and / or, the epoxy equivalent is 650-1200; and / or, the viscosity is 500cps-2000cps.

[0034] More preferably, when the D of the aqueous epoxy emulsion is 50 When the diameter is 67.5nm-72.5nm, the epoxy equivalent is 950-1100, and the viscosity is 500cps-1500cps, the comprehensive performance of the water-based epoxy thick paste coating is better.

[0035] Using a small amount of organic solvent to dissolve the first epoxy resin is conducive to more complete emulsification of the epoxy resin, wherein the organic solvent is preferably propylene glycol methyl ether (PM), and the first epoxy resin is selected from at least one of solid E20 epoxy resin, E44 epoxy resin, and E51 epoxy resin, preferably solid E20 epoxy resin.

[0036] It should be noted that the first epoxy resin and the second epoxy resin may be the same or different, and the present invention is not limited thereto.

[0037] In order to cooperate with the aqueous epoxy emulsion with high solid content, preferably, the aqueous nano-composite dispersion slurry comprises nano powder, aqueous wetting dispersant and water, and the solid content of the aqueous nano-composite dispersion slurry is 20%-40%.

[0038] In order to further improve the stability of the waterborne epoxy mastic coating, the particle size of the nano powder in the waterborne nano composite dispersion slurry is preferably 50nm-100nm.

[0039] Specifically, the nano powder is preferably at least one of nano magnesium hydroxide, nano zinc oxide, and nano graphene, and more preferably a mixed powder of nano magnesium hydroxide, nano zinc oxide, and nano graphene. The water is preferably deionized water.

[0040] In one embodiment, the filler includes a physical filler and an anti-rust filler, and the mass ratio of the physical filler to the anti-rust filler is 5:4-15:4.

[0041] Specifically, the physical filler includes at least one of titanium dioxide, feldspar powder, mica powder, kaolin, silica powder, and precipitated barium sulfate.

[0042] The anti-rust filler includes at least one of aluminum tripolyphosphate, high-purity zinc phosphate, iron titanium powder, ferrophosphorus powder, and mica iron oxide.

[0043] In one embodiment, the auxiliary agent includes but is not limited to at least one of a co-solvent, a defoamer, a dispersant, a wetting agent, a toughening agent, and an anti-flash rust agent.

[0044] Preferably, the A component includes 30%-40% of aqueous epoxy emulsion, 3%-10% of aqueous nanocomposite dispersion slurry, 12%-30% of body filler, 8%-20% of anti-rust filler, 0.5%-1% of cosolvent, 0.2%-1% of defoamer, 1%-2% of dispersant, 0.2%-1% of wetting agent, 0.2%-1% of toughening agent, 0.2%-1% of mildewproofing agent, 0.2%-1% of neutralizing agent, 0.5%-2% of film former, 0.5%-2% of anti-flash rust agent, 0.5%-2% of rheological additive and 5%-25% of water.

[0045] Specifically, the co-solvent includes at least one of ethylenediamine, ethylene glycol butyl ether, and propylene glycol butyl ether.

[0046] The defoaming agent includes at least one of mineral oil, silicone, and non-ionic polymer defoaming agent.

[0047] The dispersant includes at least one of sodium dodecylbenzene sulfonate, sodium hexametaphosphate, and triethanolamine oleate.

[0048] The wetting agent includes at least one of sodium salt of dioctyl sulfonated succinate of organic silicon, fatty alcohol polyoxyalkyl ether, and fatty alcohol polyoxyethylene ether.

[0049] The toughening agent includes at least one of tricresyl phosphate, alkyl phosphate, and silane coupling agent KH560.

[0050] The mildew preventer comprises at least one of o-phenylphenol, bisthiocarbamate and 1,2-benzisothiazolinone.

[0051] The neutralizing agent includes at least one of dimethylethanolamine, dodecylamine, and 2-amino-2-methyl-1-propanol;

[0052] The film-forming agent includes at least one of alcohol ester dodecanedione, propylene glycol butyl ether, and dipropylene glycol methyl ether.

[0053] The flash rust prevention agent includes at least one of a titanate coupling agent, a dibenzoguanidine chromate, and an organic zinc complex.

[0054] The rheological additive includes at least one of a cellulose thickener, an organic bentonite, a polyurethane thickener, and an alkali swelling thickener.

[0055] When the waterborne epoxy mastic coating is used, in order to achieve a better curing film-forming effect after the two components are mixed, the mass ratio of component A to component B is preferably 5:1-8:1.

[0056] In one embodiment, the preparation method of component A in the waterborne epoxy mastic coating comprises the following steps:

[0057] S1, providing a water-based epoxy emulsion and a water-based nanocomposite dispersion slurry;

[0058] S2, mixing the filler, the additive and the water and grinding them to obtain a grinding slurry;

[0059] S3, sequentially mixing the grinding slurry with the aqueous nanocomposite dispersion slurry, the aqueous epoxy emulsion and part of the auxiliary agent to obtain component A.

[0060] In step S1, in order to obtain an aqueous epoxy emulsion with a high solid content, the present invention provides a method for preparing an aqueous epoxy emulsion, which comprises the following steps: heating and melting a second epoxy resin and a polyetheramine to obtain an aqueous epoxy emulsifier; dissolving the first epoxy resin with an organic solvent, and mixing the mixture with the aqueous epoxy emulsifier to obtain a mixture; dispersing the mixture until the phase is inverted, adding water and continuing to disperse to obtain an aqueous epoxy emulsion.

[0061] Preferably, the temperature of the heating and melting reaction is 80°C-135°C, and the time is 1.5h-3.5h.

[0062] In step S2, in order to make the grinding slurry mixed evenly and free of dry powder particles, it is preferred to first add the rheological additive organic bentonite into the water and mix it until it is in a uniform paste state, and then add the defoamer, dispersant, and wetting agent in sequence. After stirring evenly, add the anti-rust pigment and physical filler in sequence, and adjust the rotation speed to 800r / min-1000r / min, and mix and grind to obtain the grinding slurry.

[0063] Specifically, the temperature of the grinding outlet is less than or equal to 55° C., and the fineness of the grinding slurry is less than or equal to 30 μm.

[0064] It should be noted that there is no fixed order for preparing step S1 and step S2. Step S1 can be performed first and then step S2, or step S2 can be performed first and then step S1. Step S1 and step S2 can also be performed simultaneously, and the present invention is not limited to this.

[0065] In step S3, in order to mix the water-based epoxy emulsion evenly while maintaining the oil-in-water liquid phase state, the mixing speed is adjusted to 300 r / min-500 r / min.

[0066] In order to adjust the pH value to 8-9, the A component also includes a neutralizer.

[0067] Considering the comprehensive performance of the waterborne epoxy high build coating, the component A further comprises at least one of an anti-flash rust agent, a defoaming agent, a toughening agent, a cosolvent, a mildew preventer and a film former.

[0068] In order to adjust the Stormer viscosity of the prefabricated coating to 90 kU-110 kU (23±2° C.), water and rheological additives may be appropriately added.

[0069] Hereinafter, the waterborne epoxy mastic coating and the preparation method thereof will be further described through the following specific examples.

[0070] Example 1

[0071] At 120°C, propylene glycol methyl ether, solid E20 epoxy resin and M3085 polyetheramine emulsifier in a mass ratio of 3:1 were added to a four-necked flask and heated for reaction for 3 hours. After reaching the reaction time, the product was transferred to a dispersion tank. At 50°C, 9g of propylene glycol methyl ether was used to dissolve 65g of solid E20 epoxy resin, and 5.5g of water-based epoxy emulsifier was added. The dispersion was sheared at 1000r / min, and 20.5g of deionized water was slowly added to obtain a water-based epoxy emulsion. The water-based epoxy emulsion was in the form of a white emulsion. 50 The nanostructured carbon fiber has a molecular weight of 72.5 nm, an epoxy equivalent of 950, a viscosity of 700 cps, and a solid content of 70.5%.

[0072] Magnesium hydroxide, zinc oxide and graphene, all with a particle size of 60 nm, are uniformly mixed with an aqueous wetting dispersant and deionized water to obtain an aqueous nanocomposite dispersion slurry with a solid content of 22.5%.

[0073] Add 153g of deionized water to the batching tank, start stirring, add 5g of rheological additive organic bentonite and stir until it becomes a uniform paste without dry powder particles; add 2.4g of mineral oil defoamer XP-10, 15g of dispersant, and 3.8g of wetting agent in sequence, stir evenly, then add 140g of anti-rust filler (APW-II aluminum tripolyphosphate, high-purity zinc phosphate) and 280g of physical filler (titanium dioxide, precipitated barium sulfate, feldspar powder) in sequence, adjust the speed to 800r / min, disperse evenly, and grind with a sand mill to obtain a grinding slurry with a fineness of less than or equal to 30μm.

[0074] The rotation speed was adjusted to 300 r / min, 50 g of aqueous nanocomposite dispersion slurry and 300 g of aqueous epoxy emulsion were mixed, 2 g of neutralizer was added to adjust the pH value to 8, 564.2 g of grinding slurry was added, and after stirring evenly, 8 g of anti-flash rust agent FA179, 3 g of mineral oil defoamer XP10, 3.5 g of toughening agent, 2 g of mildewproofing agent, 6.6 g of cosolvent, 13.7 g of film-forming aid were added, and the viscosity was adjusted to 95 kU (23 ± 2 ° C) with 6 g of deionized water and 6 g of rheological additive to obtain component A.

[0075] During use, component A with a mass ratio of 5:1 is mixed with cashew nut shell oil-modified phenolic amine curing agent HD-5003 to obtain a water-based epoxy high paste coating.

[0076] Example 2

[0077] At 120°C, propylene glycol methyl ether, solid E20 epoxy resin and M3085 polyetheramine emulsifier in a mass ratio of 4:1 were added to a four-necked flask and heated for reaction for 3 hours. After reaching the reaction time, the product was transferred to a dispersion tank. At 50°C, 65g of solid E44 epoxy resin was dissolved with 9g of propylene glycol methyl ether, and 2g of water-based epoxy emulsifier was added. The dispersion was sheared at 1000r / min until the phase inversion, and 24g of deionized water was slowly added to obtain a water-based epoxy emulsion. The water-based epoxy emulsion was in the form of a white emulsion. 50 The nanostructured carbon fiber has an epoxy equivalent of 950, a viscosity of 1000 cps, and a solid content of 66.5%.

[0078] Magnesium hydroxide, zinc oxide and graphene, all with a particle size of 60 nm, are uniformly mixed with an aqueous wetting dispersant and deionized water to obtain an aqueous nanocomposite dispersion slurry with a solid content of 22.5%.

[0079] Add 138g of deionized water to the batching tank, start stirring, add 5g of rheological additive organic bentonite and stir until it becomes a uniform paste without dry powder particles; add 2.4g of mineral oil defoamer XP-10, 15g of dispersant, and 3.8g of wetting agent in sequence, stir evenly, then add 200g of anti-rust pigment (APW-II aluminum tripolyphosphate, high-purity zinc phosphate) and 200g of physical filler (titanium dioxide, precipitated barium sulfate, feldspar powder) in sequence, adjust the speed to 800r / min, and after uniform dispersion, grind with a sand mill to obtain a grinding slurry with a fineness of less than or equal to 30μm.

[0080] The rotation speed was adjusted to 300 r / min, 50 g of aqueous nanocomposite dispersion slurry and 335 g of aqueous epoxy emulsion were mixed, 2 g of neutralizer was added to adjust the pH value to 8, 564.2 g of grinding slurry was added, and after stirring evenly, 8 g of anti-flash rust agent FA179, 3 g of mineral oil defoamer XP10, 3.5 g of toughening agent, 2 g of mildewproofing agent, 6.6 g of cosolvent, 13.7 g of film-forming aid were added, and the viscosity was adjusted to 100 kU (23 ± 2 ° C) with 6 g of deionized water and 6 g of rheological additive to obtain component A.

[0081] During use, component A with a mass ratio of 7:1 is mixed with cashew nut shell oil-modified phenolic amine curing agent HD-5003 to obtain a water-based epoxy high-build coating.

[0082] Example 3

[0083] At 120°C, propylene glycol methyl ether, solid E20 epoxy resin and NP8836 polyether nonionic emulsifier in a mass ratio of 5:1 were added to a four-necked flask and heated for reaction for 3 hours. After reaching the reaction time, the product was transferred to a dispersion tank. At 50°C, 66g of solid E51 epoxy resin was dissolved with 10g of propylene glycol methyl ether, and 3.3g of water-based epoxy emulsifier was added. The dispersion was sheared at 1000r / min until the phase inversion, and 20.7g of deionized water was slowly added to obtain a water-based epoxy emulsion. The water-based epoxy emulsion was in the form of a white emulsion. 50 The nanostructured carbon fiber has a molecular weight of 69.7 nm, an epoxy equivalent of 950, a viscosity of 900 cps, and a solid content of 69.2%.

[0084] Magnesium hydroxide, zinc oxide and graphene, all with a particle size of 70 nm, are uniformly mixed with an aqueous wetting dispersant and deionized water to obtain an aqueous nanocomposite dispersion slurry with a solid content of 20.5%.

[0085] Add 118g of deionized water to the batching tank, start stirring, add 5g of rheological additive organic bentonite and stir until it becomes a uniform paste without dry powder particles; add 2.4g of mineral oil defoamer XP-10, 15g of dispersant, and 3.8g of wetting agent in sequence, stir evenly, then add 140g of anti-rust pigment (APW-II aluminum tripolyphosphate, high-purity zinc phosphate) and 280g of physical filler (titanium dioxide, precipitated barium sulfate, feldspar powder) in sequence, adjust the speed to 800r / min, and after uniform dispersion, grind with a sand mill to obtain a grinding slurry with a fineness of less than or equal to 30μm.

[0086] The rotation speed was adjusted to 300 r / min, 60 g of aqueous nanocomposite dispersion slurry and 390 g of aqueous epoxy emulsion were mixed, 2 g of neutralizer was added to adjust the pH value to 8, 499.2 g of grinding slurry was added, and after stirring evenly, 8 g of anti-flash rust agent FA179, 3 g of mineral oil defoamer XP10, 3.5 g of toughening agent, 2 g of mildewproofing agent, 6.6 g of cosolvent, 13.7 g of film-forming aid were added, and the viscosity was adjusted to 105 kU (23 ± 2 ° C) with 6 g of deionized water and 6 g of rheological additive to obtain component A.

[0087] During use, component A with a mass ratio of 8:1 is mixed with cashew nut shell oil-modified phenolic amine curing agent HD-5003 to obtain a water-based epoxy high paste coating.

[0088] Example 4

[0089] The only difference between Example 4 and Example 1 is that the mass ratio of the solid E20 epoxy resin to the M3085 polyetheramine emulsifier in the epoxy emulsifier is 8:1.

[0090] Example 5

[0091] The only difference between Example 5 and Example 1 is that the mass ratio of the solid E20 epoxy resin to the M3085 polyetheramine emulsifier in the epoxy emulsifier is 2.5:1.

[0092] Comparative Example 1

[0093] The difference between Comparative Example 1 and Example 1 is that 260 g of aqueous epoxy emulsion is mixed with 150 g of aqueous nanocomposite dispersion slurry, and 504.2 g of grinding slurry is added.

[0094] Comparative Example 2

[0095] The only difference between Comparative Example 2 and Example 1 is that 400 g of aqueous epoxy emulsion is mixed with 10 g of aqueous nanocomposite dispersion slurry, and 504.2 g of grinding slurry is added.

[0096] Comparative Example 3

[0097] The only difference between Comparative Example 3 and Example 1 is that the self-emulsifying waterborne epoxy curing agent 38-1 (solid content 70%, viscosity 15000 cps) produced by Huntsman is used.

[0098] The waterborne epoxy thick paste coatings prepared in Examples 1-5 and Comparative Examples 1-3 were tested for physical and chemical indicators and performance, and the results are shown in Table 1.

[0099] Table 1

[0100]

[0101] According to Table 1, the solid content of the waterborne epoxy thick paste coating described in the present invention is as high as over 70%, and the VOC content is lower than 60g / L, which is much lower than the national standard GBT35602-2017 "Green Product Evaluation (Coating)", HJ / T5176-2017 "Waterborne Anticorrosion Coating for Steel Structure" and GB30981-2020 "Limits of Hazardous Substances in Industrial Protective Coatings". The service life of the coating can meet the requirements of ISO12944 standard: Under C3~C4 corrosion environment conditions, the service life of the coating reaches the maximum requirement of the design life, and complies with the limitations of standards such as HG / T4759-2014 "Waterborne Epoxy Resin Anticorrosion Coating", QCR581-2017 "Technical Conditions for Coatings for Railway Passenger Cars", JT / T695-2007 "Technical Conditions for Anticorrosion of Surface Coatings of Concrete Bridge Structures" and HGT5176-2017 "Waterborne Anticorrosion Coating for Steel Structures".

[0102] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0103] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A waterborne epoxy high build coating, characterized in that: The waterborne epoxy thick paste coating comprises component A and component B; The component A comprises 30%-40% of an aqueous epoxy emulsion, 3%-10% of an aqueous nanocomposite dispersion slurry, 20%-50% of a filler, 4%-15% of an auxiliary agent, and 5%-25% of water. The aqueous epoxy emulsion comprises 2%-8% of an aqueous epoxy emulsifier, 60%-70% of a first epoxy resin, 5%-18% of an organic solvent, and 20%-30% of water. The aqueous epoxy emulsifier is an adduct of a second epoxy resin and an emulsifier in a mass ratio of 3:1-5:

1. The emulsifier is selected from a PLR1801C nonionic emulsifier or a NP8836 polyether nonionic emulsifier, and the D 50 The aqueous nanocomposite dispersion slurry comprises nano powder, aqueous wetting dispersant and water, wherein the nano powder is selected from at least one of nano magnesium hydroxide, nano zinc oxide and nano graphene; The B component is a cashew nut shell oil modified phenolic amine curing agent.

2. The waterborne epoxy mastic paint according to claim 1, characterized in that: When the waterborne epoxy mastic paint is used, the mass ratio of component A to component B is 5:1-8:

1.

3. The waterborne epoxy mastic coating according to claim 1, characterized in that: The epoxy equivalent of the waterborne epoxy emulsion is 650-1200; And / or, the viscosity of the aqueous epoxy emulsion is 500cps-2000cps.

4. The waterborne epoxy mastic coating according to claim 1, characterized in that: The first epoxy resin is selected from at least one of solid E20 epoxy resin, E44 epoxy resin, and E51 epoxy resin; And / or, the second epoxy resin is selected from at least one of solid E20 epoxy resin, E44 epoxy resin, and E51 epoxy resin.

5. The waterborne epoxy mastic paint according to claim 1, characterized in that: The solid content of the aqueous nanocomposite dispersion slurry is 20%-40%.

6. The waterborne epoxy mastic coating according to claim 1, characterized in that: The particle size of the nano powder is 50nm-100nm.

7. The waterborne epoxy mastic paint according to claim 1, characterized in that: The filler comprises a physical filler and an anti-rust filler, and the mass ratio of the physical filler to the anti-rust filler is 5:4-15:

4.

8. The waterborne epoxy mastic paint according to claim 1, characterized in that: The component A comprises 30%-40% of aqueous epoxy emulsion, 3%-10% of aqueous nanocomposite dispersion slurry, 12%-30% of body filler, 8%-20% of anti-rust filler, 0.5%-1% of cosolvent, 0.2%-1% of defoamer, 1%-2% of dispersant, 0.2%-1% of wetting agent, 0.2%-1% of toughening agent, 0.2%-1% of mildewproofing agent, 0.2%-1% of neutralizing agent, 0.5%-2% of film former, 0.5%-2% of anti-flash rust agent, 0.5%-2% of rheological additive and 5%-25% of water.

Citation Information

Patent Citations

  • Nano modified aqueous epoxy rust-resisting paint and production method thereof

    CN102796436A

  • Waterborne epoxy emulsifier, preparation method and application thereof

    CN113896896A